Comparison of Femoral and Internal Jugular Vein Cannulation for Rapid Resuscitation during Cardiopulmonary Arrest - Kashif, Sanum (Pakistan Armed Forces Medical Journal, 2023)
Objective: To compare Femoral and Internal jugular veins for rapid fluid and drug administration during ongoing cardiopulmonary resuscitation. Study Design: Prospective longitudinal study. Place and Duration of Study: Intensive Care Unit, Frontier Corps Hospital, Quetta Pakistan, from Aug 2019 to Jan 2020. Methodology: After Ethical Committee Approval, 60 consecutive critical patients of ICU were inlcuded and divided into Femoral and Internal Jugular Groups as per the catheterization they received during cardiopulmonary resuscitation. The landmark technique was used in both groups. Success rate along with complications were compared between groups. Results: In the Femoral (F) Group, cannulation was successful in 28 patients (93.3%) out of 30 patients, whereas in the Internal Jugular (I) Group, out of 30 patients, 22(73.3%) patients were successfully cannulated. Inadvertent carotid and femoral artery punctures occurred in 6 patients (20.0%) in the Internal Jugular-Group and one patient (3.3%) in the Femoral-Group, respectively. In contrast, soft tissue injury occurred due to more than one attempt in 5 patients (16.7%) in the Internal JugularGroup and two patients (6.7%) in the Femoral-Group. Conclusion: The study concluded that femoral vein cannulation is superior to internal jugular cannulation for successful resuscitation in critical care patients without disruption of chest compression and, therefore, should be the method of choice in these patients.